2003
DOI: 10.1177/0148607103027005374
|View full text |Cite
|
Sign up to set email alerts
|

Total parenteral nutrition, an ally in the management of patients with intestinal failure and malnutrition: a long‐term view

Abstract: Jonathan Rhoads, MD, devoted his career to efforts designed to improve supportive patient care. He was a pioneer in the development of parenteral nutrition, continuing with determination despite daunting clinical challenges. The research efforts of Dr. Rhoads and his colleagues in addressing and remedying nutritional obstacles in surgical patients, including hypoproteinemia and infused-volume constraints, helped pave the way toward the collaborative development of total parenteral nutrition and elevated surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In 1968, Dudrick and Rhodes spearheaded the use of high‐energy parenteral nutrition called hyperalimentation 3 . Subsequently, PN became the major route of nutritional support on both sides of the Atlantic 4–6 . Over the next two decades, a number of studies consisting of small controlled trials suggested that PN was harmful and promoted increased sepsis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1968, Dudrick and Rhodes spearheaded the use of high‐energy parenteral nutrition called hyperalimentation 3 . Subsequently, PN became the major route of nutritional support on both sides of the Atlantic 4–6 . Over the next two decades, a number of studies consisting of small controlled trials suggested that PN was harmful and promoted increased sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…3 Subsequently, PN became the major route of nutritional support on both sides of the Atlantic. [4][5][6] Over the next two decades, a number of studies consisting of small controlled trials suggested that PN was harmful and promoted increased sepsis. Consequently, EN is now recommended as the preferred route of nutritional support in critically ill patients.…”
Section: Introductionmentioning
confidence: 99%